Comparative growth of the intertidal barnacle Tetraclita stalactifera (Thoracica: Tetraclitidae) in sites influenced by upwelling and tropical conditions at the Cabo Frio region, Brazil - Felipe Skinner, Luís; Neves Siviero, Fernanda; Coutinho, Ricardo (Revista de Biología Tropical, 2007)
Growth of the intertidal barnacle Tetraclita stalactifera was compared in two sites under upwelling and tropical influence at Cabo Frio region, Brazil. The hypothesis was that growth is higher at sites with an enhanced productivity. Five quadrates of 10 x 10 cm were cleared in an intertidal zone of each site to follow growth from recruitment and onwards. Base diameters were measured for 18 individuals at the tropical site (Ponta da Fortaleza) and 22 at the upwelling site (Ponta da Cabeça) using digitalized photos and ImageTool software. Mean growth rates were 0.07 mm/day at the tropical site and 0.06 mm/day at the site under upwelling influence. No effect of location, upwelling season or settlement time was found on barnacle growth rates. Other factors or synergic interactions such as temperature and food availability could influence T. stalactifera growth.